Traditional Chinese medicine for hypertrophic scars-A review of the therapeutic methods and potential effects - Daqin Chen; Qiannan Li; Huimin Zhang; Fang Kou; Qiang Li; Chunming Lyu; Chunming Lyu; Hai Wei (Frontiers Media S.A., 2022)
Hypertrophic scar (HS) is a typical pathological response during skin injury, which can lead to pain, itching, and contracture in patients and even affect their physical and mental health. The complexity of the wound healing process leads to the formation of HS affected by many factors. Several treatments are available for HS, whereas some have more adverse reactions and can even cause new injuries with exacerbated scarring. Traditional Chinese Medicine (TCM) has a rich source, and most botanical drugs have few side effects, providing new ideas and methods for treating HS. This paper reviews the formation process of HS, the therapeutic strategy for HS, the research progress of TCM with its relevant mechanisms in the treatment of HS, and the related new drug delivery system of TCM, aiming to provide ideas for further research of botanical compounds in the treatment of HS, to promote the discovery of more efficient botanical candidates for the clinical treatment of HS, to accelerate the development of the new drug delivery system and the final clinical application, and at the same time, to promote the research on the anti-HS mechanism of multiherbal preparations (Fufang), to continuously improve the quality control and safety and effectiveness of anti-HS botanical drugs in clinical application.